Clinical and laboratory features, complications and treatment outcome of brucellosis in childhood and review of the literature - Uluğ, Mehmet; Yaman, Yöntem; Yapıcı, Ferda; Can-Uluğ, Nuray (The Turkish Journal of Pediatrics, 2011)
Brucellosis, whether in an endemic region or not, remains a diagnostic puzzle due to occasional misleading unusual presentations and non-specific symptoms. The aim of this study was to evaluate the clinical and laboratory findings, complications and treatment outcome of brucellosis in children in southeastern Anatolia, Turkey. This study focuses on the frequency of clinical and laboratory findings and complications in cases with brucellosis. Of 22 patients, 8 (36.3%) were female and 14 (63.7%) were male. Fever, malaise, lack of appetite, arthralgia, and night sweating were the main presenting symptoms overall. Hematologic complications (n=13, 59.1%) were most common, followed by skeletal (n=7, 31.8%) and cutaneous system (n=1, 4.5%). Brucellosis may affect any organ system and imitate a variety of clinical entities. Diagnosis of brucellosis should be considered whenever there is a febrile illness associated with rheumatological complaints. Consequently, early recognition of the infection, prolonged antibiotic treatment and careful long-term follow-up should improve the patient outcome.